(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The increasing dependence on digital platforms and information technologies has led to the emergence of cybercrimes that disproportionately target women. As India advances technologically, incidents of online abuse, harassment, privacy invasion, and digital exploitation of women have risen sharply. The Indian Constitution, through its provisions and judicial interpretations, offers various safeguards aimed at protecting women’s dignity, privacy, and freedom in cyberspace. This review explores the constitutional and legal frameworks governing cybercrimes against women, including key provisions under Articles 14, 19, and 21, and landmark judgments such as Shreya Singhal v. Union of India. It also highlights the growing significance of the right to privacy & freedom of expression in the digital age. The study emphasizes the urgent need for stronger enforcement mechanisms, judicial vigilance, and public awareness to ensure that cyberspace remains a secure and equitable platform for women. By examining constitutional guarantees, legislative measures, and judicial perspectives, this paper seeks to underline the importance of upholding women’s rights and human dignity in the evolving digital environment.